2014
DOI: 10.1016/j.jnucmat.2014.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Surface morphology and deuterium retention in tungsten and tungsten–rhenium alloy exposed to low-energy, high flux D plasma

Abstract: Surface topography and deuterium retention in polycrystalline warm-rolled W and W-5%Re depending on the exposure temperature, are formed on the W and W-5%Re surfaces. In the W-5%Re, the deuterium retention demonstrates its maximum at exposure temperature of 463 K, while in the W this maximum is shifted to 523 K. A difference in the temperature dependence of the D retention for the W and W-5%Re is explained, as a rough approximation, by temperature dependences of the ductility of these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…According to the TDS measurements immediately performed after the plasma exposure, an increase in the exposure temperature from 573 to 773 K led to a decrease in the amount of released deuterium from 3.9 × 10 20 to 4.7 × 10 18 D m −2 (table 2). This decrease in the amount of deuterium correlated well with previously published data on the retention of deuterium in undamaged tungsten samples exposed to low-energy (76 eV), high-flux (about 5 × 10 21 m −2 s −1 ) deuterium plasma [30,31]. The accumulation of deuterium in undamaged polycrystalline hot-rolled tungsten exposed to deuterium plasma with ion energies well below the displacement threshold can be explained by the mechanisms of fracture and/or plastic deformation due to deuterium supersaturation [32].…”
Section: Resultssupporting
confidence: 90%
“…According to the TDS measurements immediately performed after the plasma exposure, an increase in the exposure temperature from 573 to 773 K led to a decrease in the amount of released deuterium from 3.9 × 10 20 to 4.7 × 10 18 D m −2 (table 2). This decrease in the amount of deuterium correlated well with previously published data on the retention of deuterium in undamaged tungsten samples exposed to low-energy (76 eV), high-flux (about 5 × 10 21 m −2 s −1 ) deuterium plasma [30,31]. The accumulation of deuterium in undamaged polycrystalline hot-rolled tungsten exposed to deuterium plasma with ion energies well below the displacement threshold can be explained by the mechanisms of fracture and/or plastic deformation due to deuterium supersaturation [32].…”
Section: Resultssupporting
confidence: 90%
“…Recently, a few experimental works have been performed to investigate the influence of solute atoms on the hydrogen retention in tungsten. These experiments clearly showed that the solute atoms can significantly change the hydrogen retention in tungsten [22][23][24][25][26][27][28]. Therefore, the study of solutehydrogen (solute-H) interaction has an important role in the reliable predication of hydrogen recycling and retention in tungsten, particularly in its alloy.…”
Section: First-principles Calculations Of Transition Metal Solute Int...mentioning
confidence: 96%
“…Further, the vacancy clusters could also act as nucleation sites for the Re/Os clusters, and mediate the diffusion of them, leading to the growth of Re/Os-rich clusters [22]. It is found that Re also has an effect on deuterium (D) in W [26][27][28]. The retention of D is much lower in W-Re than that in W [28], which may be attributed to that Re blocks the nucleation of vacancies by forming a Re-vacancy (Re-V) complex or enhances the recombination between vacancy and self-interstitial atoms (SIAs).…”
Section: Behaviors Of Transmutation Elements Re and Os And Their Effe...mentioning
confidence: 99%